Advances in membrane tafficking and endosomal signaling of G protein-coupled receptors - Hanyaloglu,AC (International Review of Cell and Molecular Biology, 2018)
The integration of GPCR signaling with membrane trafficking, as a single orchestrated system, is a theme increasingly evident with the growing reports of GPCR endosomal signaling. Once viewed as a mechanism to regulate cell surface heterotrimeric G protein signaling, the endocytic trafficking system is complex, highly compartmentalized, yet deeply interconnected with cell signaling. The organization of receptors into distinct plasma membrane signalosomes, biochemically distinct endosomal populations, endosomal microdomains, and its communication with distinct subcellular organelles such as the Golgi provides multiple unique signaling platforms that are critical for specifying receptor function physiologically and pathophysiologically. In this chapter I discuss our emerging understanding in the endocytic trafficking systems employed by GPCRs and their novel roles in spatial control of signaling. Given the extensive roles that GPCRs play in vivo, these evolving models are starting to provide mechanistic understanding of distinct diseases and provide novel therapeutic avenues that are proving to be viable targets.